2015
DOI: 10.1590/1980-5497201500060012
|View full text |Cite
|
Sign up to set email alerts
|

Recomendações e práticas dos comportamentos saudáveis entre indivíduos com diagnóstico de hipertensão arterial e diabetes no Brasil: Pesquisa Nacional de Saúde (PNS), 2013

Abstract: ABSTRACT:Objective: To analyze healthy life style recommendations given in health care and the adoption of healthy behaviors among hypertension and diabetes patients. Methods: We analyzed the recommendations according to the place of the last health care visit (primary health care, other public facilities, and private health care facilities). The effects of having a diagnosis of hypertension or diabetes on the adoption of healthy practices were analyzed by multivariate logistic regression models, using sex, ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
7

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 19 publications
0
5
0
7
Order By: Relevance
“…Estudos já apontaram a relação entre o conhecimento e a atitude de práticas saudáveis: as pessoas reconhecem a importância da adoção destas práticas, mas poucos mostram motivação concreta para adotá-las 37,45 . É necessário considerar os determinantes da escolha do estilo de vida, que muito provavelmente tem relações arraigadas no prazer sentido ao praticar alguns hábitos que são considerados não saudáveis 34 .…”
Section: Tabelaunclassified
“…Estudos já apontaram a relação entre o conhecimento e a atitude de práticas saudáveis: as pessoas reconhecem a importância da adoção destas práticas, mas poucos mostram motivação concreta para adotá-las 37,45 . É necessário considerar os determinantes da escolha do estilo de vida, que muito provavelmente tem relações arraigadas no prazer sentido ao praticar alguns hábitos que são considerados não saudáveis 34 .…”
Section: Tabelaunclassified
“…26 These results reaffirm the evidence from a study developed with data from the 2013 National Health Survey: individuals with diabetes prioritize ending harmful habits, such as eating sweets, using tobacco and alcohol, adopting new habits/ practices that bring health benefits and contribute to glycemic control, such as regular physical activity or adequate consumption of fruits and vegetables. 27 Regarding foot care, the frequency of poor selfcare adherence with scores lower than those of several studies was found. 3,6,28 It is emphasized that to prevent foot complications, some care is essential, such as: daily examination of the feet for edema, erythema, callus, discoloration, cuts or perforations, and excessive dryness; maintaining hygiene, careful drying, especially between the toes, cutting nails straight, without leaving tips, and not wearing tight shoes.…”
Section: Methods Objective Introductionmentioning
confidence: 71%
“…24 Já dados recentes da Pesquisa Nacional de Saúde mostraram que ter diagnóstico de DM diminuiu significativamente o comportamento "uso atual de produtos de tabaco", mas principalmente o "consumo frequente de doces". 25 Assim, conforme identificado na presente pesquisa, os pacientes com DM2 parecerem acreditar que as restrições alimentares se configuram, mais fortemente, como ações de controle da doença que a própria cessação do tabaco. Nesse sentido, acredita-se ser necessário que ações mais incisivas de combate ao tabagismo entre pacientes com DM2 sejam levadas a cabo, favorecendo o entendimento de que o uso do tabaco também se relaciona a complicações e agravos da doença.…”
Section: Para Quem Tem Diabetes Não é Tanto Questão De Cigarro O Queunclassified